"An Unfollowable World": Beowulf, English Poetry, and the Phenomenalism of Language. Issue 7 (4th July 2013) - Christie, E. J.
Abstract This essay traces a history of Beowulf criticism, specifically focusing on the cultural value and literary merit that are always to some extent opposed in describing the poem's worth. It investigates assumptions about the relationships between language, poetry, and culture that informed, and sometimes continue to inform, Beowulf criticism. On the one hand, Beowulf is taken to represent an essential Englishness, while on the other hand it is linguistically alien to modern speakers. Beowulf thus forms an ideal litmus test for foundational questions such as "what makes language literary?" and "what makes a poem an English poem?" Although Beowulf is often represented as an outlier, a poem which we must learn to understand in its own terms, this survey demonstrates that Beowulf criticism reflects predictable trends in the evolution of thought about the relationship between language, literature, and culture.